(untitled) (Revista Educação, Artes e Inclusão, 2024)
The present work of a qualitative nature presents a review of the legislation that regulates andgoverns the teaching of art in Brazil, showing its achievements and impasses in the light of someauthors who dialogue with regulatory frameworks in the educational field. It continues with theobservation and confrontation of the existing curricula for a degree in art in the State of SantaCatarina with regard to the specificity of the languages that are offered. A questionnaire was sent toart teachers from the microregion of Joinville - São Francisco do Sul, Schroeder, Araquari,Balneário Barra do Sul, Corupá, Garuva, Guaramirim, Itapoá, Jaraguá do Sul, Joinville andMassaranduba - who work in professional and technological education integrated to high school,allowing the emergence of a brief portrait of their experiences in the classroom. From a past withmultipurpose educators to the contemporary recognition of the specificities of the four artisticlanguages, going through several stages, it is noted that there is still uncertainty about what art isand who is better prepared to teach it. Furthermore, the disruption of schools persists with the lackof materials and equipment in addition to the disregard of educational institutions.